Cidades de vidro: a fotografia de Chichico Alkmim e o registro da tradição e da mudança em Diamantina. 1900 a 1940 - Dayse Lucide Silva Santos (2015)
The purpose of this project, from a Social and Cultural History perspective is to understand Chichico Alkmim´s (1886 -1978) view when he portrayed Diamantina through his camera . In order to better understand how life was in Diamantina from 1900 to 1940, Alkmim´s pictures were used During his life, Francisco Augusto Alkimim built a comprehensive collection of 5,349 glass negatives, from which 369 of them, portraying Diamantina, were used. The concept of Diamantina as a national heritage is based in many images, which gave the place both sense and meaning Such images can be seen as a pictorial reconstruction of Diamantina as a "religious" place, "beyound the gold and local trade" and "the heritage part". All of these ideas come together as a background for both the innovation and tradition in Diamantina. This project used different academic studies with Diamantina as a subject, taking into a account the concepts given by both Economical History and Social History as well studies accomplished by Reinhart Kosekkecj Walter Benjamim, Carlos fortuna, dominique Poulot and Peter burke added lots of information about the town, its heritage and how people see it. This project, which is based in Regional History, intends to add more information to the local photography, to the place itself and its heritage.